Consecration of the Parsee Mazagaon Anjuman Daremeher - Mumbai Archive Project Team (Jio Institute, 2024)
The Parsee Mazagaon Anjuman Daremeher was originally consecrated on January 20, 1907, as prominently indicated on its façade. It was built under the supervision of Mancherjee Pallonjee, with generous contributions from the Parsi community of Mumbai.